2018
DOI: 10.1021/acs.jctc.8b00031
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Monte Carlo Methods for Modeling Proteins Including Computation of Absolute Free Energies of Binding

Abstract: The generation of a complete ensemble of geometrical configurations is required to obtain reliable estimations of absolute binding free energies by alchemical free energy methods. Molecular dynamics (MD) is the most popular sampling method, but the representation of large biomolecular systems may be incomplete owing to energetic barriers that impede efficient sampling of the configurational space. Monte Carlo (MC) methods can possibly overcome this issue by adapting the attempted movement sizes to facilitate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 73 publications
1
54
0
Order By: Relevance
“…One of the major challenges in modern computational biochemistry is the accurate and reliable calculation of affinities between proteins and associated binding partners . A very prominent method to calculate free‐energy changes upon a ligand binding to a host protein or DNA is to simulate a nonphysical path where the ligand is alchemically perturbed in the protein and free in solution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges in modern computational biochemistry is the accurate and reliable calculation of affinities between proteins and associated binding partners . A very prominent method to calculate free‐energy changes upon a ligand binding to a host protein or DNA is to simulate a nonphysical path where the ligand is alchemically perturbed in the protein and free in solution .…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges in modern computational biochemistry is the accurate and reliable calculation of affinities between proteins and associated binding partners. [1][2][3][4][5][6][7][8] A very prominent method to calculate free-energy changes upon a ligand binding to a host protein or DNA is to simulate a nonphysical path where the ligand is alchemically perturbed in the protein and free in solution. [9] In combination with the employment of a thermodynamic cycle, the free-energy change along the nonphysical path is the same as the free-energy change along the physical path.…”
Section: Introductionmentioning
confidence: 99%
“…In a reproducibility study involving four different implementations of relative hydration free energy calculations, the authors found in many cases statistically significant ΔΔ differences on the order of 0.2 kcal/mol [27]. Systematic differences of the same order of magnitude were detected in a recent study comparing Monte Carlo and Molecular Dynamics sampling for binding free energy calculations [24], although, in this case, differences in water models and periodic boundary conditions might confound the analysis.…”
Section: Disagreements Between Methodologies Impact Force Field Develmentioning
confidence: 89%
“…Secondly, changing the potential energy of the system used to simulate the bound and unbound states means changing the theoretical free energy Δ , which makes it harder to detect systematic biases introduced by the methodologies. There are several examples in the literature noting differences in binding free energy predictions between different methods, but in which it was impossible to determine whether this was due to other differences in the model or system preparation, insufficient sampling, or shortcomings of the methodology [22][23][24][25]. Consequently, it is important to test the methods on the same set of molecular systems, using the same model.…”
Section: Comparing the Efficiency Of Methods Requires Eliminating Conmentioning
confidence: 99%
See 1 more Smart Citation